Financial literacy, attitude, and fintech payment in an Islamic perspective: mediating role of financial self-efficacy in students’ personal finance - Hamdan Adib; Naila Intania (Journal of Islamic Economics Management and Business (JIEMB), 2025)
In Indonesia, members of Generation Z encounter notable difficulties in regulating their personal finances, largely attributable to inadequate financial literacy and pronounced consumerist behavior, even though the utilization of financial technology is steadily expanding. The present research investigates how financial literacy, financial attitudes, and fintech-based payment systems influence students’ ability to manage their finances, while considering financial self-efficacy as an intermediary construct. The study adopts a quantitative explanatory design and surveys 120 students from the Faculty of Islamic Economics and Business at IAI Khozinatul Ulum Blora, selected through stratified random sampling procedures. Data were obtained via a five-point Likert-type questionnaire and subsequently processed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The empirical results indicate that financial attitudes significantly enhance self-efficacy but exert no direct effect on financial management. Conversely, financial literacy shows a robust impact on financial management, whereas financial self-efficacy does not mediate the examined relationships. Fintech payment plays a dual function by simultaneously strengthening self-efficacy and exerting a direct positive influence on students’ financial management practices. Overall, the findings underscore the pivotal contribution of financial technology in directing students’ financial conduct in the digital age, while revealing differentiated patterns of influence for literacy and attitudes.